Toward the development of dual-targeted glyceraldehyde-3-phosphate dehydrogenase/trypanothione reductase Inhibitors against Trypanosoma brucei and Trypanosoma cruzi - Belluti, Federica; Uliassi, Elisa; Veronesi, Giacomo; Bergamini, Christian; Kaiser, Marcel; Brun, Reto; Viola, Angelo; Fato, Romana; Michels, Paul A. M.; Krauth-Siegel, Renate; Cavalli, Andrea; Bolognesi, Maria Laura (ChemMedChem, 2014)
A significant improvement in the treatment of trypanosomiases has been achieved with the recent development of nifurtimox-eflornithine combination therapy (NECT). As an alternative to drug combinations and as a means to overcome most of the antitrypanosomatid drug discovery challenges, a multitarget drug design strategy has been envisaged. To begin testing this hypothesis, we designed and developed a series of quinone-coumarin hybrids against glyceraldehyde-3-phosphate dehydrogenase/trypanothione reductase (GAPDH/TR). These enzymes belong to metabolic pathways that are vital to Trypanosoma brucei and Trypanosoma cruzi, and have thus been considered promising drug targets. The synthesized molecules were characterized for their dual-target antitrypanosomal profile, both in enzyme assays and in in vitro parasite cultures. The merged derivative 2-[3-(3-dimethylaminopropoxy)-2-oxo-2H-chromen-7-yl]oxyanthracene-1,4-dione (10) showed an IC50 value of 5.4 μM against TbGAPDH and a concomitant Ki value of 2.32 μM against TcTR. Notably, 2-4-[6-(2-dimethylaminoethoxy)-2-oxo-2H-chromen-3-yl]phenoxyanthracene-1,4-dione (compound 6) displayed a remarkable EC50 value for T. brucei parasites (0.026 μM) combined with a very low cytotoxicity toward mammalian L6 cells (7.95 μM). This promising low toxicity of compound 6 might be at least partially due to the fact that it does not interfere with human glutathione reductase.
Gesehen am 25.09.2020